2015
DOI: 10.3389/fpls.2015.00693
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing in transgenic plants

Abstract: Epigenetic silencing is a natural phenomenon in which the expression of genes is regulated through modifications of DNA, RNA, or histone proteins. It is a mechanism for defending host genomes against the effects of transposable elements and viral infection, and acts as a modulator of expression of duplicated gene family members and as a silencer of transgenes. A major breakthrough in understanding the mechanism of epigenetic silencing was the discovery of silencing in transgenic tobacco plants due to the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 84 publications
5
87
0
2
Order By: Relevance
“…Unlike TGS however, PTGS is often reversible and used as a quick acting regulator of transcript half-life and subsequent gene expression [152]. The molecular processes of both TGS and PTGS have both been well characterized and are not in the scope of this review, and for further information please see the review by Rajeekumar et al [153]. Numerous studies have also reported transgene silencing in rice [154][155][156].…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…Unlike TGS however, PTGS is often reversible and used as a quick acting regulator of transcript half-life and subsequent gene expression [152]. The molecular processes of both TGS and PTGS have both been well characterized and are not in the scope of this review, and for further information please see the review by Rajeekumar et al [153]. Numerous studies have also reported transgene silencing in rice [154][155][156].…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…These limitations could be overcome by genetic modifications that allow the dominant expression of a transgene carrying the desired trait or allele, or alternatively the dominant down‐regulation of endogenous genes by silencing. Down‐regulation strategies, albeit efficient, may pose problems in the long run since the endogenous genes are still expressed, leading to potential instability of the desired trait after several generations (Rajeevkumar et al ., 2015). Recently, the development of genome‐editing strategies allowed selective site‐directed mutagenesis even in large polyploid genomes, providing a very attractive approach to creating new stable alleles in crops.…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic plants with an inverted transgene repeat could be problematic, both from a practical and from regulatory point of view. First, two or more insertions of transgenes often result in epigenetic transgene silencing in subsequent plant generations (Kumpatla and Hall, ; Rajeevkumar et al ., ). Second, using an inverted transgene cassette repeat in breeding programs or crop production would require a regulatory approval of uncertain, but likely negative outcome.…”
Section: Discussionmentioning
confidence: 97%